Analisis Faktor-faktor yang Mempengaruhi Ketimpangan Wilayah di Provinsi DKI Jakarta dan Provinsi Kalimantan Timur Tahun 2010-2020 - Binta Azida Fahma; Robertus Mulyo Hendarto (Universitas Diponegoro, 2022)
Regional inequality is a development problem experienced by Indonesia. DKI Jakarta Province as the capital city of Indonesia and East Kalimantan Province which is designated as a candidate for the new capital city of Indonesia has a high inequality. This study aims to analyze the effect of investment, agglomeration, unemployment rate, primary sector GRDP distribution and road length on regional inequality in DKI Jakarta Province and East Kalimantan Province in 2010‒2020. This study uses the Ordinary Least Square (OLS) regression analysis method and uses a data processing tool in the form of the Eviews 10 application. The data used in this analysis is time series data in 2010-2020 obtained from the BPS, BPS DKI Jakarta and BPS Kalimantan Timur. The study indicates that in the Province of DKI Jakarta the investment variable has a positive and significant influence on regional inequality. The agglomeration variable, the unemployment rate has a negative and significant effect on regional inequality, while the primary sector GRDP distribution and road length variables have no significant effect on regional inequality. Meanwhile, in East Kalimantan Province, the variables of agglomeration, unemployment rate and distribution of GRDP in the primary sector have a positive and significant effect on regional inequality, while the investment variables and road length have no significant effect on regional inequality. Investment variables, agglomeration, unemployment rate, primary sector GRDP distribution and road length together have a positive and significant impact on regional inequality in DKI Jakarta Province and East Kalimantan Province in 2010-2020.